2006
DOI: 10.1097/01.pec.0000199563.64264.3a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Etomidate on Intracranial Pressure and Systemic Blood Pressure in Pediatric Patients with Severe Traumatic Brain Injury

Abstract: In pediatric patients with severe traumatic brain injury, single-dose etomidate administration resulted in statistically significant reductions in ICP and improvement in cerebral perfusion pressure without significantly altering MAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The size of this cohort is similar to (or larger than) those of several therapeutic studies cited in the most recent expert guidelines(15, 19, 25-28). Collecting data near-continuously uniquely strengthened our study by increasing the volume and precision of our data while objectively determining unbiased periods of intracranial hypertension(10).…”
Section: Discussionsupporting
confidence: 67%
“…The size of this cohort is similar to (or larger than) those of several therapeutic studies cited in the most recent expert guidelines(15, 19, 25-28). Collecting data near-continuously uniquely strengthened our study by increasing the volume and precision of our data while objectively determining unbiased periods of intracranial hypertension(10).…”
Section: Discussionsupporting
confidence: 67%
“…Although some authors proposed to avoid using etomidate due to high risk adrenal insufficiency [60], a study, in pediatric patients with severe head injury, revealed that etomidate treatment reduced intracranial pressure [61]. STZ-induced oxidative stress model is used in this study in order to simulate oxidative stress situation in different neurological pathologies such as trauma or Control STZ STZ+Etomidate STZ+Vehicle Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, Moss and colleagues demonstrated the efficacy of etomidate in causing a significant ICP reduction with a minimal reduction in MAP and CPP [39]. Similarly, in pediatrics, Bramwell and colleagues demonstrated that a single dose of etomidate is effective at reducing ICP while maintaining MAP and CPP [40]. However, the use of etomidate is currently being reviewed in TBI patients because of its potent effects on the adrenal axis-leading to relative adrenal insufficiency in animals and in some clinical reports.…”
Section: Contraindications Hypersensitivitymentioning
confidence: 93%